2002
DOI: 10.1063/1.1526922
|View full text |Cite
|
Sign up to set email alerts
|

Formation of oriented nanocrystals in an amorphous alloy by focused-ion-beam irradiation

Abstract: Articles you may be interested inProducing metastable nanophase with sharp interface by means of focused ion beam irradiation J. Appl. Phys. 105, 044305 (2009); 10.1063/1.3079508 Focused ion beam induced synthesis of a porous antimony nanowire network Crystallographic features of oriented nanocrystals induced by focused-ion-beam irradiation of an amorphous alloy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 12 publications
0
34
1
Order By: Relevance
“…For micro/nano features, FIB irradiation can induce a change in density and may introduce a nanocrystalline structure, depending on the irradiation conditions [44][45][46]. However, the dimensions of such a formed nanocrystalline structure would be around 10nm [45,46]; this would not improve the wear resistance of the BMG because the crystal size is too small to support normal loads [40]. In addition, the size effect may be taken into account when considering the fatigue behavior of micro/nano features.…”
Section: Wear Of Bulk Metallic Glass Materials During Molding Processmentioning
confidence: 99%
“…For micro/nano features, FIB irradiation can induce a change in density and may introduce a nanocrystalline structure, depending on the irradiation conditions [44][45][46]. However, the dimensions of such a formed nanocrystalline structure would be around 10nm [45,46]; this would not improve the wear resistance of the BMG because the crystal size is too small to support normal loads [40]. In addition, the size effect may be taken into account when considering the fatigue behavior of micro/nano features.…”
Section: Wear Of Bulk Metallic Glass Materials During Molding Processmentioning
confidence: 99%
“…19) We found that electron irradiation can induce nanocrystallization of an amorphous phase in metallic glasses in which nanostructure cannot be easily realized by thermal annealing. 14,20) The metastable nanocrystalline phase was formed from an amorphous phase by electron irradiation 21,22) and the formation of crystallographically orientated nanocrystals under FIB irradiation 16) was reported. These novel results imply that electron irradiation to an amorphous phase is a new method to obtain the controlled nanocrystalline structure in metallic glasses.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization of the amorphous phase is induced not only by thermal annealing but other external factors such as electron irradiation, 14,15) focused ion beam (FIB), 16) electropulsing 17,18) and high pressure. 19) We found that electron irradiation can induce nanocrystallization of an amorphous phase in metallic glasses in which nanostructure cannot be easily realized by thermal annealing.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The formation of crystallographically orientated nanocrystals under focused ion beam (FIB) irradiation was reported. 10) Metallic glasses are known to show glass-to-liquid (G-L) transition and a supercooled liquid region can be maintained above the glass transition temperature (T g ). Table 2 shows the results of electron-irradiation induced crystallization in Zr-based metallic glasses reported to date.…”
Section: Introductionmentioning
confidence: 99%